Incidence and Risk Factors of Mastitis in Shiraz, Iran: Results of a Cohort Study - Zarshenas, M.; Zhao, Y.; Poorarian, S.; Binns, Colin; Scott, Jane (Mary Ann Liebert, Inc. Publishers, 2017)
BACKGROUND: Approximately one in five Western women who breastfeed are likely to experience acute mastitis. This study investigated the incidence and risk factors of acute mastitis in a cohort of Iranian women. SUBJECTS AND METHODS: Subjects were 672 participants of the Shiraz Infant Feeding Study conducted between June 2014 and March 2015. Mothers were recruited from the maternity ward and followed up at 1, 3, 4, and 6 months postpartum to obtain information on their breastfeeding practices and experiences. The occurrence of acute mastitis in the first 26 weeks postpartum was self-reported and the occurrence of acute mastitis in the first 4 weeks and between 5 and 12 weeks postpartum was treated as separate outcomes. The risk factors for acute mastitis were explored using multivariable logistic regression analysis. RESULTS: In total, 130 mothers (19.3%, 95% confidence interval: 16.3-22.3%) experienced at least one episode of acute mastitis. Having expressed breast milk and use of a pacifier were significantly associated with acute mastitis in both the first 4 weeks and between 5 and 12 weeks postpartum. Persistent problems with cracked or sore nipples, or engorged breasts, and a reduction in breastfeeding were associated with acute mastitis between 5 and 12 weeks. CONCLUSIONS: The incidence of acute mastitis experienced by this cohort of Iranian women is similar to that reported for women in Western countries. The risk factors of acute mastitis identified in this study are potentially modifiable and could be prevented or ameliorated with adequate support and anticipatory guidance provided in the early postpartum period.